Kebebasan Hakim Dalam Penjatuhan Pidana Korupsi Dikaitkan Dengan Surat Edaran Mahkamah Agung Nomor 3 Tahun 2018 - Hamdi Pune; Elsa Rina Maya Toule; Erwin Ubwarin (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Judges must be free to conduct legal considerations, and feel confident in what they are trying, so that they can impose sentences according to their beliefs and are supported by two pieces of evidence, but the Circular Letter of the Supreme Court Number 3 of 2018, limits judges in making decisions.Purposes of the Research: To analyze and discuss the freedom of judges in making decisions on a criminal act, as well as analyze and discuss the freedom of judges associated with the Circular Letter of the Supreme Court Number 3 of 2018 in criminal acts of corruption.Methods of the Research: The research is normative juridical, using primary and secondary legal materials.Results of the Research: From the results Based on the results of the research, it was found that the Circular Letter of the Supreme Court Number 3 of 2018 binds judges to, and restricts judges from making decisions, but there are judges who follow this circular letter and some do not follow the circular letter, according to with the amount of state losses arising from the corruption committed.